Reaktualisasi Ajaran Islam: Studi atas Pemikiran Hukum Munawir Sjadzali - Ilyas, Yunahar (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2006)
Referring to Ibn Qayyim al-Jawziyya and AbÅ« YÅ«suf, Munawir Sjadzali says that it is necessary to make use of rational thought based on social context in reasoning and applying a legal rule. It is historical that Caliph âUmar has practiced this principle in connection with the case of land loot. Instead of taking the land of Syrians as loot, the Caliph âUmar took tax from the land owners and distributed the money for military. In another chance, Caliph âUmar stopped giving zakÄh to muâallaf group because there is no longer need to give them zakÄh in the current situation, different from what Prophet Muhammad and Caliph AbÅ« Bakr have practiced. According to Sjadzali, there are a lot of Islamic legal issues to which an intensive attention and contextualization should be drawn, such as the law of inheritance, zakÄh for muâallaf, bank interest, woman leadership, woman testimony, inter-religious marriage, non Muslim status, slavery, et cetera. The main idea of Sjadzaliâs thought is the necessity to take social and cultural context of the society into account at comprehending, and then concluding a legal decision from, Quranic verses concerning with social life, though this will led to not apply the extrinsic meaning of those verses.